Inhibition of growth of human mammary tumor cells by potent antagonists of luteinizing hormone-releasing hormone. - Sharoni, Y (1989)
Various studies support the view that analogs of luteinizing hormone-releasing hormone (LH-RH) exert some direct effects on mammary tumor cells. Recently, new LH-RH antagonists [Ac-D-Nal(2)1,D-Phe(pCl)2,D-Trp3,D-Hci6,D-Ala10]-LH-RH (SB-29) and [Ac-D-Nal(2)1,D-Phe(pCl)2,D-Trp3,D-Cit6,D-Ala10]LH-RH (SB-30), which are devoid of edematogenic effects, were synthesized. In this study, we examined whether these LH-RH antagonists inhibit the proliferation of MDA-MB-231 human mammary tumor cells in culture. [3H]Thymidine incorporation into DNA and cell number were measured. The antagonists induced up to 40% inhibition of [3H]thymidine incorporation in MDA-MB-231 cells. This inhibition was dose-dependent in the 0.3-30 microM range and could be demonstrated after 2 days of incubation in the presence of the peptides. An older antagonist, [Ac-D-Phe(pCl)1,2,D-Trp3,D-Arg6,D-Ala10]-LH-RH (ORG 30276), had a lesser effect, and the agonist des-Gly10-[D-Ser(tBu)6]LH-RH ethylamide (buserelin) had no effect. The antagonists SB-29 and SB-30 also inhibited the rate of cell growth, as measured by cell number, while the LH-RH agonist buserelin had no significant effect. These results support the concept that these new LH-RH antagonists can directly inhibit the growth of human mammary tumors and thus might be suitable for the treatment of breast cancer.